2017
DOI: 10.17221/180/2016-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of Carum copticum essential oil against Streptococcus mutans and Streptococcus sobrinus isolated from canine dental plaque

Abstract: Dental caries is amongst the most prevalent oral diseases in both humans and dogs. Streptococcus mutans and Streptococcus sobrinus (mutans streptococci) are the major cariogenic bacteria isolated from dental caries. Since these bacteria generally show resistance to common antibiotics, natural products such as plant essential oils could be a good substitute. For this study, we aimed to evaluate the antibacterial activity of Carum copticum essential oil against Streptococcus mutans and Streptococcus sobrinus. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The prevalence of Streptococcus mutans and Streptococcus sobrinus in canine dental plaque was previously studied (Nouri Gharajalar & Hassanzade, 2017). These bacteria were isolated from 40% and 10% of tested samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Streptococcus mutans and Streptococcus sobrinus in canine dental plaque was previously studied (Nouri Gharajalar & Hassanzade, 2017). These bacteria were isolated from 40% and 10% of tested samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Also, MIC50 and MBC values of the essential oil against S. mutans isolates were 20 µg/ml and 80 µg/ml, respectively, and the mean ± SD of zone inhibition was 5 ± 31 and 2 ± 10 for 80 µg/ml and 20 µg/ml concentrations of the essential oil, respectively. The result of this study indicated an increase in the inhibition zone with increased concentrations of T. ammi essential oil [13]. Another study assessed the antibacterial activity of T. ammi oil against the oral microbes using an agar well diffusion assay with three concentrations, 40 µl/ml, 80 µl/ml, and 100 µl/ml.…”
Section: Discussionmentioning
confidence: 87%
“…Twenty-five µl reactions comprised a ready-to-use master mix (Reddy, Sinaclone, Iran), and S mutans ATCC 25175 and S. sobrinus ATCC 33478 were included in the assays as positive controls. The amplicons were resolved by electrophoresis in 1.5% agarose gels [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Nouri et al (2017) studied the prevalence of cariogenic bacteria in dog dental plaques and identified Streptococcus mutans and Streptococcus sobrinus in 8 (40%) and 2 (10%) of samples, respectively. Most of the isolates displayed multidrug resistance patterns to the antibiotics used in the study [17].…”
Section: Discussionmentioning
confidence: 99%